Corporate cash hoarding in a model with liquidity constraints - Falk Mazelis (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper studies the role of uncertainty in the corporate cash hoarding puzzle. The baseline model is a stochastic neoclassical growth model featuring idiosyncratic and uninsurable technology shocks and a cash-in-advance constraint on new investments on the individual firm level. Individual agents' choices regarding cash holdings are analyzed and the effects of the introduction of a financial sector explored. The resulting aggregate cash holdings of households are non-optimal compared to the complete markets solution and aggregate excess cash increases with uncertainty. Aggregate consumption is also higher, but the added volatility of consumption decreases lifetime utility. Since cash holdings are usually managed by the financial sector, the results suggest a link between firm level risk and the behavior of the banking system.
Keywords: C63; E21; E41; 330